The Thought of Ibn Taymiyyah as a Framework for Critical Thinking in Islamic Education in the Post-Truth Era - Rahmaisya Surbakti; Nabila Ramadhani Harahap; Nabila Humairoh; Asrini Harahap; Kacar Ginting; Rahmah Walidaini (Sekolah Tinggi Agama Islam Al-Jami Banjarmasin, 2026)
This study aims to analyze the relevance of Ibn Taymiyyah’s thoughts on critical thinking to the development of Islamic education in the post-truth era. The study employs a qualitative approach using a descriptive-analytical method through library research. Data were obtained from various relevant literature on Ibn Taymiyyah’s thought, Islamic education, and the post-truth phenomenon, and were analyzed using content analysis. The results of the study indicate that Ibn Taymiyyah’s concept of critical thinking rooted in criticism of excessive ta’wil, rejection of blind adherence (taqlid), and the emphasis on the importance of ijtihad remains relevant in addressing the challenges of contemporary Islamic education. These concepts can be applied through the harmonization of reason and revelation, guided inquiry-based learning, and the application of the tabayyun method in dealing with the flow of digital information, thereby fostering students who are critical, selective, and responsible.